Mechanism of axial strain effects on friction in carbon nanotube rotating bearings. (5th June 2018) - Huang, Jianzhang; Han, Qiang
Abstract: A systematic study of axial strain effects on friction in carbon nanotube bearings is conducted in this paper. The relationships between friction and axial strains are determined by implementing molecular dynamics simulations. It is found that the dependence of friction on velocity and temperature is altered by axial strains. The mechanism of strain effects is revealed through numerical and theoretical analyses. Based on phonon computations, axial strain effects tune friction by adjusting the distribution of the phonon frequency density, which affects the transfer efficiency of orderly kinetic energy into disorderly thermal energy. The findings in this work advance the understanding of friction in carbon nanotubes and suggest the great potential of axial strain effects on tuning friction in nanodevice applications.